Male Bowhead Whale Reproductive Histories Inferred from Baleen Testosterone and Stable Isotopes. Issue 1 (4th May 2022) - Hunt, Kathleen E; Buck, C Loren; Ferguson, Steven H; Fernández Ajo, Alejandro; Heide-Jørgensen, Mads Peter; Matthews, Cory J D
Synopsis: Male mammals of seasonally reproducing species typically have annual testosterone (T) cycles, with T usually peaking during the breeding season, but occurrence of such cycles in male mysticete whales has been difficult to confirm. Baleen, a keratinized filter-feeding apparatus of mysticetes, incorporates hormones as it grows, such that a single baleen plate can record years of endocrine history with sufficient temporal resolution to discern seasonal patterns. We analyzed patterns of T every 2 cm across the full length of baleen plates from nine male bowhead whales ( Balaena mysticetus ) to investigate occurrence and regularity of T cycles and potential inferences about timing of breeding season, sexual maturation, and reproductive senescence. Baleen specimens ranged from 181–330 cm in length, representing an estimated 11 years (smallest whale) to 22 years (largest whale) of continuous baleen growth, as indicated by annual cycles in stable isotopes. All baleen specimens contained regularly spaced areas of high T content (T peaks) confirmed by time series analysis to be cyclic, with periods matching annual stable isotope cycles of the same individuals. In 8 of the 9 whales, T peaks preceded putative summer isotope peaks by a mean of 2.8 months, suggesting a mating season in late winter / early spring. The only exception to this pattern was the smallest and youngest male, which had T peaks synchronous with isotope peaks. This smallest, youngest whale also did not have T peaks in the first half of the plate, suggesting initiation of T cycling during the period of baleen growth. Linear mixed effect models suggest that whale age influences T concentrations, with the two largest and oldest males exhibiting a dramatic decline in T peak concentration across the period of baleen growth. Overall, these patterns are consistent with onset of sexual maturity in younger males and possible reproductive senescence in older males. We conclude that adult male bowheads undergo annual T cycles, and that analyses of T in baleen may enable investigation of reproductive seasonality, timing of the breeding season, and life history of male whales.